Keterampilan Komunikasi dan Agresivitas Siswa - Malik, M Abdul (Psikopedagogia, 2016)
This study aimed to know how big the influence of communication skills to aggressiveness. This was a correlational study. This study was conducted in SMA Negeri 4 Yogyakarta. The sample of this study was seventy students who were taken through simple random sampling technique. This study employed the Aggressiveness Scale and the Communication Skill Scale. The data were analyzed by using statistical regression analysis. The result of this study showed that the communication skills affected the aggressiveness. This study proved that communication skills were able to repress the students’ aggressiveness. Therefore, the counselors are expected to assist the development of students’ communication skills.